2021
DOI: 10.3390/medicina57060566
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Quercetin on Oxidative Stress-Induced Tubular Epithelial Damage in the Experimental Rat Hyperoxaluria Model

Abstract: Background and Objectives: The most common kidney stones are calcium stones and calcium oxalate (CaOx) stones are the most common type of calcium stones. Hyperoxaluria is an essential risk factor for the formation of these stones. Quercetin is a polyphenol with antioxidant, anti-inflammatory, and many other physiological effects. The aim of this study was to investigate the protective effect of quercetin in hyperoxaluria-induced nephrolithiasis. Materials and Methods: Male Wistar-Albino rats weighing 250–300 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It has been reported that quercetin can inhibit renal inflammation and fibrosis in UUO and LPS mouse models by decreasing expressions of IL-18, IL-1 β , TNF- α , and fibrosis area in Masson staining and inhibiting collagen expression [ 20 ]. In addition, quercetin has a protective effect on renal tubular epithelial cell injury induced by oxidative stress in hyperoxaluria rats [ 21 ]. Therefore, we verified the binding ability of the key compounds to the five core genes through molecular docking simulation, and the docking results revealed that these compounds could stably bind to the active pocket of the core protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that quercetin can inhibit renal inflammation and fibrosis in UUO and LPS mouse models by decreasing expressions of IL-18, IL-1 β , TNF- α , and fibrosis area in Masson staining and inhibiting collagen expression [ 20 ]. In addition, quercetin has a protective effect on renal tubular epithelial cell injury induced by oxidative stress in hyperoxaluria rats [ 21 ]. Therefore, we verified the binding ability of the key compounds to the five core genes through molecular docking simulation, and the docking results revealed that these compounds could stably bind to the active pocket of the core protein.…”
Section: Discussionmentioning
confidence: 99%
“…Many flavonoids such as quercitin, hyperoside, rutin, diosmin, and apigenin have been investigated for their probable potential to inhibit the formation of kidney stones. Table 1 summarizes the main findings regarding the anti-nephrolithiatic activity of flavonoids [12][13][14][15][16].…”
Section: Anti-nephrolithiatic Activity Of Bioactive Compounds 31 Flav...mentioning
confidence: 99%
“…In vivo Reduced damage due to hyperoxaluria. Reduced oxalate stone formation [12] Quercetin and hyperoside…”
Section: Quercetinmentioning
confidence: 99%
“…Inactivating NLRP3 may prevent oxalate damage by altering macrophage polarization. Antioxidant treatment of experimentally induced hyperoxaluria in rats also reduces the inflammatory responses and production of the inflammatory mediators (23,24). Indeed, inflammation in kidney stone disease can be the upstream (as a pathogenic factor) or downstream event (as a complication).…”
Section: Editorial On the Research Topic Immunity And Inflammatory Response In Kidney Stone Diseasementioning
confidence: 99%
“…Inactivating NLRP3 may prevent oxalate damage by altering macrophage polarization. Antioxidant treatment of experimentally induced hyperoxaluria in rats also reduces the inflammatory responses and production of the inflammatory mediators ( 23 , 24 ).…”
mentioning
confidence: 99%